Corporate governance mechanisms and capital structure in a two-tier board system: The role of board gender diversity - Indra Pahala; Suherman Suherman; Titis Fatarina Mahfirah; Rosle Mohidin; Rini Indriani; Gentiga muhammad zairin; Tri Hesti Utaminingtyas; Herni Kurniawati; Audia Zikra (Corporate Board: Role, Duties and Composition, 2025)
This study sought to investigate the relationship between capital structure and corporate governance variables, with an emphasis on the moderating effect of gender diversity on the board on the relationship between capital structure and corporate governance mechanisms in a two-tier board structure (Indonesia). Utilizing a sample of 384 non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2012 to 2021, this study generated 3,836 observations to evaluate hypotheses regarding the impact of the board of directors (BOD), board of commissioners (BOC), and the proportion of independent commissioners (PIC) on capital structure, as proxied by the debt-to-asset ratio (DAR) and long-term debt-to-asset ratio (LTD). Furthermore, it examined the moderating role of gender diversity in the relationship between corporate governance mechanisms and capital structure metrics. Panel data regression analysis, which comprised a fixed-effects (FE) model with clustered standard errors, was used to analyse the data. The study found no significant relationship between the corporate governance mechanisms and DAR. However, the BOD and the BOC significantly affect LTD. Incorporating gender diversity as a moderator revealed a significant enhancement in the linkage between corporate governance practices and financial leverage measures. Negative and notable associations were observed when moderated by gender diversity, indicating an amplified influence in the presence of female board members.